Gender Specific Differences of Smallholder Farm Households Perspective of Food-Energy-Land Nexus Frameworks in Ethiopia - Villamor, Grace B.; Guta, Dawit D.; Mirzabaev, Alisher (Frontiers in Sustainable Food Systems, 2020)
The water-energy-food security nexus concept is a widely recognized analytical approach to achieve sustainable development goals. However, to date, related thinking has mostly been applied at higher scales in a top-down manner, while bottom-up and local scale applications remain limited. This includes the gender dimension of the nexus, which is one of the sustainable development goals. Narrowing this gap, this paper describes and assesses the food-energy-land nexus from a smallholder farm household perspective in the context of rural Ethiopia through a gender-specific lens. To explore the differences between men and women perspective of the nexus, we adopted the Actors, Resources, Dynamics and Interactions (ARDI) to co-develop a mental model of the nexus concept combined with statistical analysis. Using this approach, we examined the key direct actors and the linkages between major resources including the processes that affect the management by gender. The results indicate that there are four aspects that differentiate male and female perspectives with respect to the water-energy-food nexus. These differences include (1) access to external actors, (2) perceptions of target resources, (3) gender specific productive roles, and (4) decision making with respect to target resource management and utilization, which may affect the dynamics and governance of the water-energy-food nexus. With regards to factors associated with time spent for collecting water and fuel and crop production vary according to gender type. Overlooking these differences could make the nexus approach unrealistic to achieve gender equity while further aggrevating the already burdening roles of women including children within households.